Clinical exuberance of classic Kaposi's sarcoma and response to radiotherapy - Jeniffer Muñoz Trujillo; Natália Ribeiro de Magalhães Alves; Paula Mota Medeiros; Luna Azulay-Abulafia; Maria de Fátima Guimarães Scotelaro Alves; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Kaposi's sarcoma (KS) is a multicentric vascular neoplasm, with cutaneous and extracutaneous involvement. Different clinical and epidemiological variants have been identified. The classic form is manifested mainly in elderly men with indolent and long-term evolution, with lesions localized primarily in the lower extremities. We present two cases of classic Kaposi's sarcoma (CKS) in two female patients with extensive, exuberant skin involvement and rapid evolution, with good response to radiotherapy.